Depoliticising the financing of higher education in fiscally challenged sub-Saharan Africa economies: the Nigerian case (2019)
The concern of this paper was to analyse the need to depoliticise the financing of higher education, and to suggest more sustainable financial channels to improving higher education financing in order to achieve an efficient and effective higher education System that is capable of performing its social and economic development functions in the competitive global market